HUBUNGAN ANTARA KEMAMPUAN BERKOMUNIKASI GURU TERHADAP KEAKTIFAN BELAJAR SISWA DI KECAMATAN MEDAN POLONIA - Nurmayani Nurmayani; Yulia Helnani Nasution (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This study aims to determine the relationship between teacher communication skills and student learning activeness in Medan Polonia sub-district, 2020/2021. This research is a correlation study using a quantitative descriptive approach. The subjects in this study were 30 teachers who were taken using the sampling technique, namely purposive sampling. The data collection techniques used were documentation and questionnaire distribution. Of the 25 statement items, only 20 items were considered valid on a 4-point Likert scale. The validity of the questionnaire was obtained from two lecturers at the Faculty of Education so that the questionnaire was deemed appropriate to be used as a research instrument. As the criteria for the variable of teacher communication skills and student learning activeness using the Likert scale. If p> 0.05, the distribution is declared normal, on the contrary, if p <0.05, the distribution is declared abnormal. The correlation results where rxy = 0.667 with significant p = 0.000 <0.050. This means that the hypothesis proposed, the stronger the teacher's communication skills, the higher the student's learning activeness is accepted. The result of the determinant coefficient (r2) of the relationship between the independent variable X and the dependent variable Y is (r2) = 0.445. This shows that the teacher's communication skills contribute to the active learning of students by 44.5%. From these results it is known that there are still 55.5% of the roles of various other factors that influence student learning activeness. Keywords: Student learning activeness, Teacher Communication.